Faktor-Faktor Penyebab Remaja Putus Sekolah Usia 12 - 18 Tahun di Polobangkeng Utara, Kabupaten Takalar - Anwar, Yulianti; Hadju, Veni; Rambulangi, Samrichard; Mastuti, Nih Luh Putu Herli (Jurnal Kebidanan Malakbi, 2022)
Dropout is a predicate given to former students who are unable to complete a level of education and unable to continue their studies to the next level of education. This study determines the factors that cause adolescents to drop out of school. This study is qualitative descriptive research with the type of field research. Data collection techniques are by conducting observations, interviews, and documentation. Meanwhile, to determine the informants using the purposive sampling technique, in this case, the researchers chose informants, namely teenagers who dropped out of school, aged 12-18 years, parents of teenagers, and the local government. The analysis used is an interactive model of data analysis technique that includes three paths specifically, data reduction, data presentation, and conclusion drawing. The results showed that the factors that caused teenagers to drop out of school were economic problems, low learning abilities, adolescent associations, and student attitudes towards teachers.